(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Below is a scientific article analyzing the experience of legalizing taxi aggregators in Uzbekistan for 2020-2025 and offering recommendations on scaling this approach to other sectors of the digital economy.